Pengaruh Variasi Penambahan Ragi Tape Dan Npk Terhadap Konsentrasi Bioetanol Hasil Fermentasi Jerami Padi - Wahyuni, Lira Aulia; Yenie, Elvi; Daud, Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
One of the alternative energy sources can be used as a substitute for fossil fuel-based energy is bioethanol. One of the raw material is rice straw ethanol. Rice straw can be used as raw material for bioethanol production because many contain cellulose. According to the Central Bureau of Statistics 2012 hay production in Indonesia reaches 64-96 million tons / year. This study aims to determine the optimal amount of yeast and NPK required in the manufacture of bioethanol once saw statistically influence of yeast and NPK against ethanol concentration produced, and test the density and viscosity of bioethanol fermented rice straw. This research was conducted by the method Separate Hydrolysis and Fermentation (SHF), with the addition of yeast transformed variables tape (5%, 10%, 15%, 20%) and the addition of NPK (0, 5%, 10%, 15%, 20% ). Bioethanol fermented bioetanolnya concentration measured using Alkoholmeter and bioethanol characteristic tests by measuring the density and viscosity. From hasi lpenelitian, obtained the highest ethanol concentration is 6% achieved on the addition of yeast 15% and 20% NPK. Density and viscosity of ethanol in the amount of 0.8482 g / ml and 1.6809 cP achieved with the addition of yeast 15% and 15% NPK.Keywords: bioethanol, rice straw, Saccharomyces cereviciae, cellulose